Cultivation Arrangements and the Cost Efficiency of Rice Farming in Taiwan - HUANG, MEI-YING; HUANG, CLIFF J.; FU, TSU-TAN (Journal of productivity analysis, 2002)
In this paper, a switching regression model is developed to analyze farmers' choice behavior and cost efficiency in field plowing arrangement in Taiwan. We find that the decision on the choice of plowing arrangement is determined by a cost comparison between self-plowing and hired-service, and other non-cost considerations, such as the availability of family labor and machinery, education level, non-farm income, age, and regional effects. Across a spectrum of farmer characteristics, empirical results indicate a potentially substantial costsavings by hiring service for field plowing than by self-plowing. Self-plowing farmers also subject to a significant level of cost inefficiency.